The Emperor Has No Clothes!: Exposing Whiteness as Explicit, Implicit, and Null Curricula. Issue 3 (27th May 2019) - Kim-Cragg, HyeRan
Abstract: This article examines the term "whiteness, " providing a historical review for context. It uncovers whiteness using educational theory that identifies three aspects of curriculum—explicit, implicit, and null. A particularly unexamined biblical interpretation itself illustrates the explicit curriculum. Visual images that permeate the culture provide examples of implicit indicators of whiteness. Episodes in our history that are not taught create a null curriculum that reveals whiteness. Finally, it suggests three educational steps with examples to expose and dismantle whiteness.